The Influence of Reputation, Professionalism, and Service Quality on Client Satisfaction in Using Tax Consulting Services - Mardiantari, Ni Komang Ayu; Budiadnyani, Ni Putu; Kustina, Ketut Tanti (Jurnal Riset Perpajakan: Amnesty, 2025)
This study aims to examine the influence of reputation, professionalism, and service quality on client satisfaction in using tax consulting services. The research was conducted with a sample of 90 corporate taxpayers registered at tax consultant offices in Denpasar City. Quantitative methods were applied with data collected through questionnaires. The analysis involved validity and reliability tests, classical assumption tests, and multiple linear regression. The results indicate that reputation positively and significantly affects client satisfaction, implying that a better reputation enhances client satisfaction. Similarly, professionalism shows a positive and significant impact, suggesting that higher levels of professional conduct by tax consultants increase client satisfaction. Furthermore, service quality also significantly influences satisfaction, highlighting the importance of timely, accurate, and responsive services. Simultaneous testing confirms that reputation, professionalism, and service quality collectively contribute significantly to client satisfaction. These findings underscore the critical role of maintaining a strong reputation, upholding professional ethics, and delivering high-quality services to foster client trust and satisfaction. Tax consultants are recommended to continuously improve service speed, maintain confidentiality, and align their services with client expectations to sustain satisfaction and loyalty. This study contributes to understanding factors that drive client satisfaction in tax consulting, providing valuable insights for practitioners and policymakers aiming to optimize tax consulting service quality in Indonesia’s evolving tax environment.